Scenario advisor tool for requirements engineering - Shin, Jae Eun; Sutcliffe, Alistair G.; Gregoriades, Andreas (My University, 2005)
This study investigates the usefulness of a scenario advisor tool which was built to help requirements engineers to generate sufficient sets of scenarios in the domain of socio-technical systems. The tool provides traceability between scenario models and requirements and helps to generate new scenarios and scenario variations. Through two series of evaluation sessions, we found that the scenario advisor tool helped users to write more sound scenarios without any domain knowledge, and to generate more variations on existing scenarios by providing specific scenario-generation hints for each scenario component. The tool should improve the reliability of requirements elicitation and validation.
Keywords: Requirements elicitation; Requirements validation; Scenario generation; Scenario schema; Traceability; Computer aided software engineering